Culturing the freshwater hydromedusa, Craspedacusta sowerbii under controlled laboratory conditions. Issue 1 (2nd January 2016) - Folino-Rorem, Nadine C.; Reid, Mark; Peard, Terry
Abstract: Craspedacusta sowerbii (phylum Cnidaria, class Hydrozoa, family Olindiiae) is an alien species with a polyp and medusa stage and originates from China. The optimal temperature range for polyp production is 19–25 °C, while medusa production and growth require warmer water (21–30 °C). Reasons for the sporadic occurrence of medusae in nature are still unclear. Culturing medusae has been problematic while culturing polyps in the laboratory is well documented. The successful culturing of C. sowerbii medusae to gonad development is only documented to our knowledge in articles in Japanese with a probable limited readership. We successfully cultured all life cycle stages of Craspedacusta, including medusae. Medusae budded from polyps from Gatun, Panama and were cultured at 23 and 26 °C using local water and Hydra Medium. Medusae bell morphology, tentacle number, gonad development, and the number and size of prey consumed were documented. Smaller medusae were hand-fed, while mature medusae captured prey. Medusae lived for 3–11 weeks and gonad development occurred. A more thorough understanding of temperature, water chemistry, and laboratory feeding protocols during all life cycle stages of C. sowerbii will aid in predicting future distribution patterns of this invasive hydroid in freshwater habitats.